1990
DOI: 10.1136/hrt.64.3.182
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate analysis in the prediction of death in hospital after acute myocardial infarction.

Abstract: Prognostic factors in patients with acute myocardial infarction based on clinical and investigative data on admission were evaluated prospectively in 111 consecutive patients. Seventeen patients (15.3%) died during hospital stay. Age, a previous infarct, high Killip class, cardiomegaly, high serum concentrations of cardiac enzymes, a low ejection fraction, and a high wall motion score index correlated significantly with in-hospital mortality; whereas sex, risk factors, and pericardial effusion did not. Multiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…As in most studies 40,41 , advanced age proved to be an important independent predictive factor of mortality. This piece of information is easily obtained and may identify high-risk patients, who may benefit from a more aggressive therapy.…”
Section: Discussionmentioning
confidence: 53%
“…As in most studies 40,41 , advanced age proved to be an important independent predictive factor of mortality. This piece of information is easily obtained and may identify high-risk patients, who may benefit from a more aggressive therapy.…”
Section: Discussionmentioning
confidence: 53%
“…This index or score is based on variables obtained during hospitalization. According to more recent studies, in-hospital mortality in acute myocardial infarction is directly related to feminine gender, older age, previous history of infarction, anterior wall AMI, extension of the ischemic area, signs of significant left ventricular dysfunction, and arterial hypotension [11][12][13][14][15] .…”
Section: Discussionmentioning
confidence: 99%
“…Both the insignificant difference in WMI and the significant difference in mortality could be explained by the significant difference in age between men and women. In a recent study, both age and WMI were shown to contain independent prognostic information [21], WMI divided the population into a defi nite low risk group (WMI > 1.3) and a medium/high risk group (fig. 1).…”
Section: Discussionmentioning
confidence: 99%